Penerapan Metode Pembelajaran “Active Learning-Small Group Discussion” di Perguruan Tinggi Sebagai Upaya Peningkatan Proses Pembelajaran - Endah Syamsiyati Nur Jannah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
The active learning approach that is carried out in the subject of Student Development in the Faculty of Islamic Sciences majoring in PAI at the Islamic University of Indonesia in the 4th semester, aims to improve student learning activeness with non-monotonous learning strategies. With this learning method, students can actively explore themselves by finding the main ideas in solving a problem, or students can apply what is learned in real life. Several learning methods can be used as alternatives to increase student activity during the learning process, one of them is